Interaction effects of drip irrigation level and planting method on water use efficiency, irrigation uniformity and yield in green pepper (Capsicum annuum L.) - Edossa, Desalegn Chemeda; Emana, Takele Gadissa (2011)
A field experiment was conducted to investigate the effects of level of irrigation and planting method on water use efficiency, irrigation uniformity and yield of drip-irrigated green pepper (Capsicum annuum L) in Bako area, Ethiopia. Three irrigation levels [50%, 75% and 100% of crop evapotranspiration (ETc)] and two planting methods (normal and paired-row planting) were applied. The experiment was laid out in a split-plot design, with irrigation levels as main plots and planting methods as subplots, in three replications. The interaction effects of the treatments on yield and water use efficiency (WUE) of green pepper were significant (p<0.05) and highly significant (p<0.01), respectively. The maximum yield (17,590 kg ha-1) and WUE (3.96 kg m-3) were recorded from treatment l100P (100% ETc with paired-row planting) while the minimum yield (4510 kg ha-1) and WUE (2.04 kg m-3) were recorded from treatment l50P (50% ETc with paired-row planting). Therefore, the study established that application of deficit irrigation system under paired-row planting method for pepper production using smallholder drip irrigation system is not favored. It was also found that both emission uniformity and wetting pattern were significantly (p<0.05) affected by irrigation levels and days after planting (DAP). The average emission uniformity (EU) of the system was found to be 89%. In general, deep percolation losses and overlapping of the wetting patterns were not evident based on the observed horizontal and vertical axes of the wetting bulbs.
Keywords: Microirrigation; Water use; Capsicum annuum